1994
DOI: 10.1079/bjn19940039
|View full text |Cite
|
Sign up to set email alerts
|

Effect of dietary protein source on feed intake, growth, pancreatic enzyme activities and jejunal morphology in newly-weaned piglets

Abstract: Seventy piglets with no access to creep feed were weaned at 28 d of age and fed on one of four diets based on either skimmed-milk powder (SMP), soya-bean-protein concentrate (SPC), soya-bean meal (SBM) or fish meal (FM). At 0, 3, 6 and 10 d after weaning, piglets were killed and the pancreas and digesta from stomach and small intestine were collected, freeze-dried and analysed for dry matter (DM), N, and trypsin (EC 3.4.21.4) and chymotrypsin (EC 3.4.21.1) activities. Small-intestinal tissue samples were taken… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
39
2
16

Year Published

2002
2002
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(61 citation statements)
references
References 22 publications
3
39
2
16
Order By: Relevance
“…These results disagree with those reported by Cera et al (1988), Makkink et al (1994), McCracken et al (1999 and Klurfeld (2002), who demonstrated a significant effect of total nutrient intake on gastrointestinal tract development; VH was directly related to dry matter and energy intake.…”
Section: Resultscontrasting
confidence: 99%
See 1 more Smart Citation
“…These results disagree with those reported by Cera et al (1988), Makkink et al (1994), McCracken et al (1999 and Klurfeld (2002), who demonstrated a significant effect of total nutrient intake on gastrointestinal tract development; VH was directly related to dry matter and energy intake.…”
Section: Resultscontrasting
confidence: 99%
“…However, important changes in the composition of the diet occur at weaning and require the presence of appropriate enzymes in the stomach, pancreas and intestine, which are usually not produced during the suckling period. As a consequence, weaning is associated with physiological and nutritional stress, which reduces feed intake and weight gain (Makkink et al, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…Overall changes in digestive organ weights during the post-weaning period (trial 1) and with changing energy intake (trial 2) were similar to those reported earlier [10,34]. The about 20% decrease in the relative weights of the large and small intestines observed in trial 1 was consistent with values ranging from 18 to 34% found in piglets weaned at later ages [5,7,19,20,26,36]. Furthermore, the mucosa was the most affected SI component, being reduced by 55%.…”
Section: Discussionsupporting
confidence: 84%
“…No entanto, Makkink et al (1994), em experimento com leitões desmamados aos 28 dias de idade e alimentados com leite em pó desnatado e concentrado protéico de soja, obtiveram peso de pâncreas superior ao dos alimentados com farelo de soja, portanto, a proteína de soja processada apresenta bons resultados de desenvolvimento pancreático nesta fase. O mesmo foi demonstrado com a inclusão de isolado protéico de soja, que não alterou o desenvolvimento pancreático.…”
Section: Resultsunclassified